Effects of Core Stability Training on Deep Stabilizing Muscle Function and Neuromuscular Control - Kyeongjin Lee (Medicina)
Background and Objectives: Pilates-based core stabilization training has garnered increasing attention for its potential to improve deep muscle activation and enhance spinal stability. This study aimed to investigate the effects of Pilates-based core stabilization training on deep stabilizing muscles using rehabilitative ultrasound imaging (RUSI). Materials and Methods: A total of 57 healthy adults aged 20 to 29 years were recruited and randomly allocated to either an experimental group (n = 29) or a control group (n = 28). Participants in the experimental group engaged in Pilates-based core stabilization training three times per week for six weeks, while the control group performed aerobic exercises. The pre- and post-intervention assessments included measurements of muscle thickness, contraction timing, and contraction ratios of the transverse abdominis (TrA), internal oblique (IO), and external oblique (EO) muscles, evaluated using RUSI. Results: The experimental group demonstrated significant improvements in TrA and IO thickness (p < 0.05), contraction timing (p < 0.05), and contraction ratios (p < 0.05) compared to the control group. The EO muscle also showed significant, albeit less pronounced, enhancements in thickness and contraction ratios. Conclusions: Pilates-based core stabilization training significantly improves core muscle function, including muscle thickness, contraction timing, and contraction ratios. These findings support the inclusion of Pilates exercises in clinical protocols aimed at enhancing core stability.